Dental hardenable composition containing transition metal adsorbent
Patent Information
- Application Number
- JP2020161104
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-26
- Filing Date
- 2020-09-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-09-25
AI Technical Summary
【0009】 本発明によれば、非反応性の無機粒子に予め第4周期の遷移金属化合物を吸着した遷移金属吸着体を採用することにより、優れた硬化性及び貯蔵安定性を有する歯科用硬化性組成物を提供することができる。
Smart Images

Figure 0007638651000001 
Figure 0007638651000002 
Figure 0007638651000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a dental hardenable composition having excellent storage stability. [Background technology]
[0002] In the dental field, hardenable compositions containing a polymerization initiator consisting of an organic peroxide and a reducing agent thereof and a polymerizable monomer are widely used as dental cements, dental adhesives, dental autopolymerizing resins, dental pretreatment materials, dental core building materials, etc.
[0003] Paste-like, individually packaged curable compositions that utilize an oxidation-reduction reaction of an organic peroxide and its reducing agent as a polymerization initiation reaction are known. Among them, individually packaged curable compositions that use benzoyl peroxide as the organic peroxide and an aromatic amine as its reducing agent have high curability and have been widely used for a long time. However, when stored under high environmental temperature conditions, they have problems such as low storage stability and discoloration to yellow or brown. As a solution to this problem, individually packaged curable compositions that use hydroperoxide, which is an organic peroxide, and a thiourea derivative, which is its reducing agent, have been disclosed (Prior Document 1). Although these individually packaged curable compositions have improved storage stability and color stability compared to compositions that use conventional polymerization initiators, their curability is insufficient. Furthermore, as a technology to overcome the above problems, a packaged curable composition has been proposed that contains a hydroperoxide, which is an organic peroxide, a thiourea derivative, which is its reducing agent, and a fourth period transition metal compound, such as a copper compound or a vanadium compound, as a polymerization accelerator (Prior Document 2). Although these packaged curable compositions have dramatically improved curability, the problem is that they have insufficient storage stability. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-292761 A [Patent Document 2] Patent Publication No. 2012-051856 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0005] Although the blending of the fourth period transition metal compound is effective in the polymerization reaction, there are problems such as reduced curability and low stability after production. [Means for solving the problem]
[0006] As a result of intensive research aimed at solving the above problems, the present inventors have discovered and completed a dental hardenable composition having excellent hardenability and storage stability by employing a transition metal adsorbent in which a fourth period transition metal compound is pre-adsorbed onto non-reactive inorganic particles. The present invention relates to (a) a fourth period transition metal compound Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. The dental curable composition comprises a transition metal adsorbent in which a fourth period transition metal compound is adsorbed onto inorganic particles, (b) a thiourea derivative, (c) an organic peroxide having a hydroperoxide group, and (d) a polymerizable monomer, wherein the (d) polymerizable monomer comprises (d-1) a polymerizable monomer not having an acidic group, and the pore volume of the non-reactive inorganic particles is 0.2 cc / g or less.
[0007] Preferably, the (d) polymerizable monomer is a dental hardenable composition further comprising (d-2) a polymerizable monomer having an acidic group. Preferably, the dental curable composition contains 1 to 40 parts by weight of (d-2) a polymerizable monomer having an acidic group, based on 100 parts by weight of the total amount of (d) the polymerizable monomer.
[0008] Preferably, the first paste comprises (a) a fourth period transition metal compound Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. The dental hardenable composition includes a transition metal adsorbent in which a fourth period transition metal compound is adsorbed onto inorganic particles, (b) a thiourea derivative, and (d) a polymerizable monomer, and the second paste includes (c) an organic peroxide having a hydroperoxide group, and (d) a polymerizable monomer. Preferably, (a) a fourth period transition metal compound Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. The adsorption amount of the fourth period transition metal compound in the transition metal adsorbent, in which the fourth period transition metal compound is adsorbed on inorganic particles, is 0.001 to 0.1 g / m 2 The dental hardenable composition is Preferably, (a) a fourth period transition metal compound is used per 100 parts by weight of the total amount of the polymerizable monomers. Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. 0.05 to 7.5 parts by weight of a transition metal adsorbent having a fourth period transition metal compound adsorbed on inorganic particles, (a) a fourth period transition metal compound Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. The dental curable composition comprises (a) 0.001 to 1 part by weight of a transition metal compound contained in a transition metal adsorbent in which a fourth period transition metal compound is adsorbed onto inorganic particles, (b) 0.1 to 4 parts by weight of a thiourea derivative, and (c) 0.1 to 3 parts by weight of an organic peroxide having a hydroperoxide group. Preferably, the dental curable composition further contains 0.5 to 350 parts by weight of a filler, 0.01 to 5 parts by weight of a photopolymerization initiator, and 0.01 to 5 parts by weight of a polymerization accelerator, relative to 100 parts by weight of the total amount of polymerizable monomers. Effect of the Invention
[0009] According to the present invention, by employing a transition metal adsorbent in which a transition metal compound of the fourth period is pre-adsorbed onto non-reactive inorganic particles, a dental hardenable composition having excellent hardenability and storage stability can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below. (a) Fourth Period Transition Metal Compound of the Present Invention Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. We describe transition metal adsorbents in which 4th period transition metal compounds are adsorbed on inorganic particles.
[0011] The transition metal compound of the fourth period refers to a metal compound of the 3rd to 12th groups of the fourth period of the periodic table, and specifically, any metal compound of scandium (Sc), titanium (Ti), vanadium (V), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), or zinc (Zn) can be used without any restrictions. Each of the above transition metal elements can have multiple valences, but as long as it has a valence that allows it to exist stably, it can be added to the curable composition of the present invention. For example, Sc (trivalent), Ti (tetravalent), V (tri-, tetra-, or pentavalent), Cr (di-, tri-, or hexavalent), Mn (di- to heptavalent), Fe (di- or trivalent), Co (di- or trivalent), Ni (divalent), Cu (mono- or divalent), or Zn (divalent). Specific examples of transition metal compounds include scandium iodide (trivalent) as a scandium compound, titanium chloride (tetravalent) and titanium (tetravalent) tetraisopropoxide as titanium compounds, vanadium acetylacetonate (trivalent), divanadium tetroxide (tetravalent), vanadyl acetylacetonate (tetravalent), vanadium stearate oxide (tetravalent), vanadyl oxalate (tetravalent), vanadyl sulfate (tetravalent), oxo-bis(1-phenyl-1,3-butanedionate)vanadium (tetravalent), and bis(maltrate)oxo-vanadium (tetravalent). ), vanadium pentoxide (5), sodium metavanadate (5), etc.; manganese compounds include manganese acetate (2), manganese naphthenate (2); iron compounds include ferrous acetate (2), ferrous chloride (2), ferrous acetate (3), ferrous chloride (3); cobalt compounds include cobalt acetate (2), cobalt naphthenate (2); nickel compounds include nickel chloride (2); copper compounds include copper chloride (1), copper bromide (1), copper chloride (2), copper acetate (2); zinc compounds include zinc chloride (2), zinc acetate (2).
[0012] Among these, trivalent or tetravalent vanadium compounds and divalent copper compounds are preferred, and trivalent or tetravalent vanadium compounds having higher polymerization promoting ability are more preferred, and tetravalent vanadium compounds are most preferred. These fourth period transition metal compounds may be used in combination of a plurality of types as necessary. The blending amount of the transition metal compound is preferably 0.001 to 1 part by weight, more preferably 0.005 to 0.5 parts by weight, relative to 100 parts by weight of the total amount of all polymerizable monomers. If the blending amount is less than 0.001 part by weight, the polymerization promoting effect is insufficient, and if the blending amount exceeds 1 part by weight, the composition may discolor or gel, resulting in reduced storage stability.
[0013] The inorganic particles non-reactive with the 4th period transition metal compound (hereinafter, also simply referred to as "non-reactive inorganic particles" in this specification) are inorganic particles non-reactive with the 4th period transition metal compound (hereinafter, also simply referred to as "transition metal compound" in this specification). Other than adsorption Inorganic particles that are not only non-reactive but also do not interact with the redox reaction between the organic peroxide and the thiourea derivative, which is the reducing agent, can be preferably used. Examples of non-reactive inorganic particles that can be used include oxides of silica, zirconia, calcium, titania, and alumina, composite oxides thereof (glass), metal fluorides such as ytterbium trifluoride and sodium fluoride, and sulfates such as magnesium sulfate and barium sulfate. Among these, composite oxides, metal fluorides, and sulfates are preferred, and among these, ytterbium trifluoride and barium sulfate are more preferred. These Other than adsorption If necessary, a plurality of types of non-reactive inorganic particles may be used in combination. Other than adsorption From the viewpoint of dispersibility, the primary particle size of the non-reactive inorganic particles is preferably 0.01 to 50 μm, and more preferably 0.01 to 20 μm. Other than adsorption If the primary particle size of the non-reactive inorganic particles is 0.01 μm or less, the particles will tend to aggregate more and will be less dispersible in the polymerizable monomer. If the primary particle size is 50 μm or more, the particles will tend to disperse unevenly in the composition, making it difficult to sufficiently promote polymerization.
[0014] In addition, there is no restriction on the shape of the particles, so long as they are non-porous, and examples of such shapes include spherical, crushed, and irregular. In the case of porous particles, the transition metal compound adsorbed in the pores has less opportunity to react as a polymerization promoter, which not only reduces the polymerization promotion efficiency, but also may cause discoloration if it remains unreacted. For this reason, Other than adsorption The pore volume of the non-reactive inorganic particles is 0.2 cc / g or less, preferably 0.15 cc / g or less, and most preferably 0.1 cc / g or less. The pore volume can be determined, for example, by the BJH method. Other than adsorption In the case where the non-reactive inorganic particles are agglomerated particles, they are of the agglomerated particles.
[0015] Other than adsorption As a method for adsorbing a transition metal compound onto non-reactive inorganic particles, either a physical adsorption method or a chemical adsorption method can be used without any restrictions. Specifically, a chemical adsorption method or a physical adsorption method such as hydrophobic adsorption, deposition precipitation method, impregnation method, coprecipitation method, ion exchange method, equilibrium adsorption method, etc. can be used, but a physical adsorption method is preferred from the viewpoint of production efficiency. More specifically, the transition metal compound is dissolved or dispersed in an organic solvent having a high affinity for the transition metal compound and a low boiling point, Other than adsorption Preferred methods include a method in which the transition metal compound is mixed with non-reactive inorganic particles and then the organic solvent is removed to obtain a transition metal adsorbent having the transition metal compound adsorbed thereon; a method in which the transition metal compound is dissolved in a good solvent having high affinity with the transition metal compound and then a poor solvent is added to precipitate the transition metal particles on the surfaces of the inorganic particles; and a method in which the transition metal compound is physically adsorbed on the surfaces of the inorganic particles using a pot mill, ball mill, planetary mill, or the like.
[0016] Other than adsorption The amount of transition metal compounds adsorbed on non-reactive inorganic particles is 0.001 to 0.1 g / m, calculated as the amount of adsorption per unit area of the inorganic particles. 2 is preferable, and more preferably 0.001 to 0.05 g / m 2 0.001g / m 2 In the cases below, the polymerization promotion effect is insufficient, and the concentration is 0.1 g / m 2In the above cases, the polymerization promoting effect is excessive, and discoloration or the like may occur, resulting in reduced storage stability. Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. In the case where the inorganic particles contain a transition metal adsorbent having a fourth period transition metal compound adsorbed thereon, any of (a) the fourth period transition metal compound Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. It is preferable that the adsorption amount of the transition metal adsorbent in which the 4th period transition metal compound is adsorbed on the inorganic particles is within the above-mentioned range, and all of the (a) 4th period transition metal compounds Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. It is more preferable that the adsorption amount in the transition metal adsorbent in which a transition metal compound of the fourth period is adsorbed onto inorganic particles is within the above range.
[0017] (a) Fourth row transition metal compounds Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. The blending amount of the transition metal adsorbent in which a transition metal compound of the fourth period is adsorbed on inorganic particles is preferably 0.05 to 7.5 parts by weight, and more preferably 0.05 to 5 parts by weight, relative to 100 parts by weight of the total amount of all polymerizable monomers. If it is less than 0.05 parts by weight, the ability as a polymerization promoter is insufficient, and if it exceeds 7.5 parts by weight, it may become localized and cause discoloration.
[0018] The (b) thiourea derivative of the present invention can be used without any restrictions as long as it is a known thiourea derivative. Specific examples of the thiourea derivative include dimethylthiourea, diethylthiourea, tetramethylthiourea, (2-pyridyl)thiourea, N-methylthiourea, ethylenethiourea, N-allylthiourea, N-allyl-N'-(2-hydroxyethyl)thiourea, N-benzylthiourea, 1,3-dicyclohexylthiourea, N,N'-diphenylthiourea, 1,3-di(p-tolyl)thiourea, 1-methyl-3-phenylthiourea, N-acetylthiourea, N-benzoylthiourea, diphenylthiourea, and dicyclohexylthiourea. Among these, N-acetylthiourea and N-benzoylthiourea are preferred. These thiourea derivatives may be used in combination as necessary. The amount of the thiourea derivative is preferably 0.1 to 4 parts by weight based on the total amount of all polymerizable monomers. If the amount is less than 0.1 part by weight, the polymerization promoting ability is insufficient, whereas if the amount exceeds 4 parts by weight, the storage stability may decrease.
[0019] The organic peroxide having a hydroperoxide group (c) of the present invention can be any known organic peroxide having a hydroperoxide group without any restrictions. Specific examples of the organic peroxide include t-butyl hydroperoxide, cyclohexyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, and the like, and cumene hydroperoxide is preferred from the viewpoint of reactivity. These organic peroxides may be used in combination of a plurality of types as necessary. The blending amount of the organic peroxide having a hydroperoxide group is preferably 0.1 to 3 parts by weight based on the total amount of all polymerizable monomers. If it is less than 0.1 part by weight, the ability as a polymerization promoter is insufficient, and if it exceeds 3 parts by weight, the storage stability may decrease.
[0020] The (d) polymerizable monomer of the present invention includes (d-1) a polymerizable monomer having no acidic group. The (d) polymerizable monomer preferably includes (d-2) a polymerizable monomer having an acidic group. The (d) polymerizable monomer may be composed only of (d-1) a polymerizable monomer having no acidic group. The polymerizable monomer (d-1) not having an acidic group of the present invention can be any known monomer having one or more polymerizable groups without any restrictions. A polymerizable monomer in which the polymerizable group exhibits radical polymerizability is preferred, and specifically, from the viewpoint of easiness of radical polymerization, the polymerizable group is preferably a (meth)acrylic group and / or a (meth)acrylamide group. In this specification, "(meth)acrylic" means acrylic and / or methacrylic, "(meth)acryloyl" means acryloyl and / or methacryloyl, and "(meth)acrylate" means acrylate and / or methacrylate.
[0021] Examples of polymerizable monomers having one radically polymerizable group and no acidic group include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, propylene glycol mono(meth)acrylate, glycerol mono(meth)acrylate, erythritol mono(meth)acrylate, N-methylol (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N,N -(dihydroxyethyl)(meth)acrylamide, methyl(meth)acrylate, ethyl(meth)acrylate, propyl(meth)acrylate, isopropyl(meth)acrylate, butyl(meth)acrylate, isobutyl(meth)acrylate, benzyl(meth)acrylate, lauryl(meth)acrylate, 2,3-dibromopropyl(meth)acrylate, 3-(meth)acryloyloxypropyltrimethoxysilane, 11-(meth)acryloyloxyundecyltrimethoxysilane, (meth)acrylamide, etc. Among these, 2-hydroxyethyl(meth)acrylate, 3-hydroxypropyl(meth)acrylate, glycerol mono(meth)acrylate, or erythritol mono(meth)acrylate is preferred because of the high affinity of the resulting hardenable composition with tooth structure.
[0022] Examples of polymerizable monomers having two radical polymerizable groups and no acidic group include 2,2-bis((meth)acryloyloxyphenyl)propane, 2,2-bis[4-(3-(meth)acryloyloxy)-2-hydroxypropoxyphenyl]propane (commonly known as "Bis-GMA"), 2,2-bis(4-(meth)acryloyloxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane), 2,2-bis(4 -(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxydiethoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxyditriethoxyphenyl)propane, 2-(4- (meth)acryloyloxydipropoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, 1,4-bis(2-(meth)acryloyloxyethyl)pyromellitate, glycerol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, 2,2,Examples of such compounds include 4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate (commonly known as "UDMA"), 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, etc. Among these, from the viewpoint of mechanical strength, 2,2-bis((meth)acryloyloxyphenyl)propane, 2,2-bis[4-(3-(meth)acryloyloxy)-2-hydroxypropoxyphenyl]propane, 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate, and 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane are preferred, and from the viewpoint of handling, triethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and glycerol di(meth)acrylate are preferred. Among 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propanes, a compound having an average added mole number of ethoxy groups of 2.6 (commonly known as "D2.6E") is preferred.
[0023] Examples of polymerizable monomers having three or more radical polymerizable groups and no acidic group include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetramethacrylate, 1,7-diacryloyloxy-2,2,6,6-tetraacryloyloxymethyl-4-oxyheptane, etc. Among these, trimethylolpropane tri(meth)acrylate is preferred because the mechanical strength of the resulting curable composition is high.
[0024] These (d-1) polymerizable monomers having no acidic group may be used in combination as necessary. From the viewpoint of improving mechanical properties, the blending amount of the polymerizable monomer having no acidic group and having two or more radical polymerizable groups is preferably set to 40-100 parts by weight, more preferably set to 60-90 parts by weight, in 100 parts by weight of the total amount of the polymerizable monomers in the curable composition. In addition, if the blending amount of the polymerizable monomer having no acidic group and having two or more radical polymerizable groups is less than 40 parts by weight, the mechanical properties may be deteriorated.
[0025] The hardenable composition of the present invention may contain (d-2) a polymerizable monomer having an acidic group for the purpose of imparting adhesiveness to a tooth structure or a prosthetic device to be placed in the oral cavity. (d-2) The polymerizable monomer having an acidic group may be any polymerizable monomer having one or more polymerizable groups and at least one acidic group such as a phosphoric acid group, a pyrophosphoric acid group, a thiophosphoric acid group, a phosphonic acid group, a sulfonic acid group, or a carboxylic acid group as the acidic group.
[0026] Examples of the polymerizable monomer having an acidic group having a phosphoric acid group include 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxybutyl dihydrogen phosphate, 5-(meth)acryloyloxypentyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 7-(meth)acryloyloxyheptyl dihydrogen phosphate, 8-(meth)acryloyloxyethyl dihydrogen phosphate, 9-(meth)acryloyloxyethyl dihydrogen phosphate, 10-(meth)acryloyloxyethyl dihydrogen phosphate, 11-(meth)acryloyloxyethyl dihydrogen phosphate, 12-(meth)acryloyloxyethyl dihydrogen phosphate, 13-(meth)acryloyloxyethyl dihydrogen phosphate, 14-(meth)acryloyloxyethyl dihydrogen phosphate, 15-(meth)acryloyloxyethyl dihydrogen phosphate, 16-(meth)acryloyloxyethyl dihydrogen phosphate, 17-(meth)acryloyloxyethyl dihydrogen phosphate, 18-(meth)acryloyloxyethyl dihydrogen phosphate, 19-(meth)acryloyloxyethyl dihydrogen phosphate, 20-(meth)acryloyloxyethyl dihydrogen phosphate, 21-(meth)acryloyloxyethyl dihydrogen phosphate, 22-(meth)acryloyloxyethyl dihydrogen phosphate, 23-(meth)acryloyloxyethyl dihydrogen phosphate, 24-(meth)acryloyloxyethyl dihydrogen phosphate, 25-(meth)acryloyloxyethyl dihydrogen phosphate, 26-(meth)acryloyloxyethyl dihydrogen phosphate, 27-(meth)acryloyloxyethyl dihydrogen phosphate, 28 p) acryloyloxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen phosphate, 20-(meth)acryloyloxyicosyl dihydrogen Phosphate, bis[2-(meth)acryloyloxyethyl]hydrogen phosphate, bis[4-(meth)acryloyloxybutyl]hydrogen phosphate, bis[6-(meth)acryloyloxyhexyl]hydrogen phosphate, bis[8-(meth)acryloyloxyoctyl]hydrogen phosphate, bis[9-(meth)acryloyloxynonyl]hydrogen phosphate, bis[10-(meth)acryloyloxydecyl]hydrogen phosphate, 1,3-di( Examples of such compounds include 2-(meth)acryloyloxypropyl dihydrogen phosphate, 2-(meth)acryloyloxyethyl phenyl hydrogen phosphate, 2-(meth)acryloyloxyethyl-2-bromoethyl hydrogen phosphate, bis[2-(meth)acryloyloxy-(1-hydroxymethyl)ethyl]hydrogen phosphate; acid chlorides, alkali metal salts, and ammonium salts thereof; and (meth)acrylamide compounds in which the ester bond of these compounds is replaced with an amide bond.
[0027] Examples of the polymerizable monomer having an acidic group having a pyrophosphate group include bis[2-(meth)acryloyloxyethyl]pyrophosphate, bis[4-(meth)acryloyloxybutyl]pyrophosphate, bis[6-(meth)acryloyloxyhexyl]pyrophosphate, bis[8-(meth)acryloyloxyoctyl]pyrophosphate, bis[10-(meth)acryloyloxydecyl]pyrophosphate; acid chlorides, alkali metal salts, and ammonium salts thereof; and (meth)acrylamide compounds in which the ester bond of these compounds is replaced with an amide bond.
[0028] Examples of the polymerizable monomer having an acidic group having a thiophosphoric acid group include 2-(meth)acryloyloxyethyl dihydrogen thiophosphate, 3-(meth)acryloyloxypropyl dihydrogen thiophosphate, 4-(meth)acryloyloxybutyl dihydrogen thiophosphate, 5-(meth)acryloyloxypentyl dihydrogen thiophosphate, 6-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 7-(meth)acryloyloxyheptyl dihydrogen thiophosphate, 8-(meth)acryloyloxyoctyl dihydrogen thiophosphate, 9-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 10-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 11-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 12-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 13-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 14-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 15-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 16-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 17-(meth)acryloyloxyheptyl dihydrogen thiophosphate, 18-(meth)acryloyloxyoctyl dihydrogen thiophosphate, 19-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 20-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 21-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 22-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 23-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 24-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 25-(meth)acryloyloxyhexyl di Examples of suitable acryloyloxynonyl dihydrogen thiophosphate include 10-(meth)acryloyloxydecyl dihydrogen thiophosphate, 11-(meth)acryloyloxyundecyl dihydrogen thiophosphate, 12-(meth)acryloyloxydodecyl dihydrogen thiophosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen thiophosphate, 20-(meth)acryloyloxyicosyl dihydrogen thiophosphate; acid chlorides, alkali metal salts, and ammonium salts thereof; and (meth)acrylamide compounds in which the ester bond of these compounds is replaced with an amide bond.
[0029] Examples of the polymerizable monomer having an acidic group having a phosphonic acid group include 2-(meth)acryloyloxyethyl phenyl phosphonate, 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, 10-(meth)acryloyloxydecyl-3-phosphonoacetate; acid chlorides, alkali metal salts, and ammonium salts thereof; and (meth)acrylamide compounds in which the ester bond of these compounds is replaced with an amide bond.
[0030] Examples of the polymerizable monomer having an acidic group having a sulfonic acid group include 2-(meth)acrylamide-2-methylpropanesulfonic acid and 2-sulfoethyl(meth)acrylate.
[0031] Examples of polymerizable monomers having an acidic group having a carboxylic acid group include (meth)acrylic compounds having one carboxyl group in the molecule and (meth)acrylic compounds having multiple carboxyl groups in the molecule. Examples of (meth)acrylic compounds having one carboxyl group in the molecule include (meth)acrylic acid, N-(meth)acryloylglycine, N-(meth)acryloylaspartic acid, O-(meth)acryloyltyrosine, N-(meth)acryloyltyrosine, N-(meth)acryloylphenylalanine, N-(meth)acryloyl-p-aminobenzoic acid, N-(meth)acryloyl-o-aminobenzoic acid, p-vinylbenzoic acid, 2-(meth)acryloyloxybenzoic acid, 3-(meth)acryloyloxybenzoic acid, 4-(meth)acryloyloxybenzoic acid, 5-(meth)acryloyloxybenzoic acid, 6-(meth)acryloyloxybenzoic acid, 7-(meth)acryloyloxybenzoic acid, 8-(meth)acryloyloxybenzoic acid, 9-(meth)acryloyloxybenzoic acid, 10-(meth)acryloyloxybenzoic acid, 11-(meth)acryloyloxybenzoic acid, 12-(meth)acryloyloxybenzoic acid, 13-(meth)acryloyloxybenzoic acid, 14-(meth)acryloyloxybenzoic acid, 15-(meth)acryloyloxybenzoic acid, 16-(meth)acryloyloxybenzoic acid, 17-(meth)acryloyloxybenzoic acid, 18-(meth)acryloyloxybenzoic acid, 19-(meth)acryloyloxybenzoic acid, 20-(meth)acryloyloxybenzoic acid, 21-(meth)acryloyloxybenzoic acid, 22-(meth)acryloyloxybenzoic acid, 23- Examples of the compound include benzoic acid, 4-(meth)acryloyloxybenzoic acid, N-(meth)acryloyl-5-aminosalicylic acid, N-(meth)acryloyl-4-aminosalicylic acid, 2-(meth)acryloyloxyethyl hydrogen succinate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxyethyl hydrogen malate; acid halides thereof; and (meth)acrylamide compounds in which the ester bond of these compounds is replaced with an amide bond.Examples of (meth)acrylic compounds having multiple carboxyl groups in the molecule include 6-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 9-(meth)acryloyloxynonane-1,1-dicarboxylic acid, 10-(meth)acryloyloxydecane-1,1-dicarboxylic acid, 11-(meth)acryloyloxyundecane-1,1-dicarboxylic acid, 12-(meth)acryloyloxydodecane-1,1-dicarboxylic acid, 13-(meth)acryloyloxytridecane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 5-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, ... Examples of the acryloyloxyethyl 3'-(meth)acryloyloxyethyl trimellitate, 4-(meth)acryloyloxybutyl trimellitate, 4-(meth)acryloyloxyhexyl trimellitate, 4-(meth)acryloyloxydecyl trimellitate, 2-(meth)acryloyloxyethyl-3'-(meth)acryloyloxy-2'-(3,4-dicarboxybenzoyloxy)propyl succinate; acid anhydrides and acid halides thereof; and (meth)acrylamide compounds in which the ester bond of these compounds is replaced with an amide bond.
[0032] Among the above-mentioned polymerizable monomers having an acidic group, those having a phosphoric acid group or a phosphonic acid group are preferred from the viewpoint of adhesiveness of the dental polymerizable composition. Among them, those having an alkyl group or an alkylene group having 4 or more carbon atoms in the main chain in the molecule are preferred, and 10-(meth)acryloyloxydecyl dihydrogen phosphate or (6-methacryloyloxy)hexyl phosphonoacetate are more preferred. These polymerizable monomers having an acidic group may be used in combination of a plurality of types as required. In addition, from the viewpoint of adhesiveness, the blending amount of the polymerizable monomer having an acidic group is preferably 1 to 40 parts by weight, more preferably 2 to 20 parts by weight, in 100 parts by weight of the total amount of all polymerizable monomers.
[0033] The curable composition of the present invention can be blended with any filler according to its intended use, without any limitations, as long as it is a known filler. For example, when used as a dental adhesive such as a dental direct restorative adhesive (bonding material) or a dental indirect restorative adhesive, or as a dental restorative material for a dental prosthesis such as a composite resin, it is preferable to blend a filler such as an inorganic filler, an organic filler, or an organic-inorganic composite filler. The filler is preferably silane-treated. By silane treatment, it is possible to fill a large amount in the composition. The silane treatment agent can be a normal silane treatment agent.
[0034] Examples of the inorganic filler include quartz, silica, silica-alumina, silica-titania, silica-zirconia, silica-magnesia, silica-calcia, silica-barium oxide, silica-strontium oxide, silica-titania-sodium oxide, silica-titania-potassium oxide, titania, zirconia, alumina, and glass fillers. More specific examples of glass fillers include silicate glass, fluoroaluminosilicate glass, fluoroboroaluminosilicate glass, and barium glass. If necessary, these inorganic fillers may be surface-treated with a silane coupling agent such as γ-methacryloxypropyltrimethoxysilane, ε-methacryloxyoctyltrimethoxysilane, or vinyltrimethoxysilane.
[0035] Examples of the organic filler include polymers such as polymethyl methacrylate, polyethyl methacrylate, methyl methacrylate-ethyl methacrylate copolymer, ethyl methacrylate-butyl methacrylate copolymer, methyl methacrylate-trimethylolpropane methacrylate copolymer, polyvinyl chloride, polystyrene, chlorinated polyethylene, nylon, polysulfone, polyethersulfone, and polycarbonate.
[0036] An example of the organic-inorganic composite filler is a pulverized composite of the inorganic oxide (inorganic filler) and the polymer (organic filler) described above.
[0037] The particle shape of the above-mentioned various fillers is not particularly limited, and may be ground particles obtained by normal grinding, or spherical particles. The particle size of these fillers is also not particularly limited, but generally, from the viewpoint of dispersibility, etc., it is preferably 100 μm or less, particularly 30 μm or less. The amount of the filler to be blended is preferably 0.5 to 350 parts by weight, more preferably 1 to 300 parts by weight, based on 100 parts by weight of the total amount of the polymerizable monomer.
[0038] A photopolymerization initiator may be blended in the curable composition of the present invention for the purpose of imparting photopolymerizability. Examples of the photopolymerization initiator include α-diketones, mono-, bis-, or trisacylphosphine oxide compounds, and mono- and diacylgermanium compounds. The blending amount of the photopolymerization initiator is not particularly limited, but from the viewpoint of photocurability, it is preferably 0.01 to 5 parts by weight, more preferably 0.1 to 3 parts by weight, based on 100 parts by weight of the total amount of the polymerizable monomers.
[0039] Examples of α-diketones include diacetyl, dibenzyl, camphorquinone, 2,3-pentadione, 2,3-octadione, 9,10-phenanthrenequinone, 4,4'-oxybenzyl, acenaphthenequinone, etc. Among these, camphorquinone is preferred because it has excellent photocurability in the visible and near ultraviolet regions and exhibits sufficient photocurability using any light source, such as a halogen lamp, a light-emitting diode (LED), or a xenon lamp.
[0040] Examples of mono-, bis- or trisacylphosphine oxide compounds include bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)(2,4,4-trimethylpentyl)phosphine oxide, bis(2,6-dimethoxybenzoyl)-n-butylphosphine oxide, bis(2,6-dimethoxybenzoyl)-(2-methylprop-1-yl)phosphine oxide, bis(2,6-dimethoxybenzoyl)-(1 ... bis(2,6-dimethoxybenzoyl)-t-butylphosphine oxide, bis(2,6-dimethoxybenzoyl)cyclohexylphosphine oxide, bis(2,6-dimethoxybenzoyl)octylphosphine oxide, bis(2-methoxybenzoyl)(2-methylprop-1-yl)phosphine oxide, bis(2-methoxybenzoyl)(1-methylprop-1-yl)phosphine oxide, bis(2,6-diethoxybenzoyl)(2-methylprop-1-yl)phosphine oxide, bis(2,6-diethoxybenzoyl)(1-methylprop-1-yl)phosphine oxide phosphine oxide, bis(2,6-dibutoxybenzoyl)(2-methylprop-1-yl)phosphine oxide, bis(2,4-dimethoxybenzoyl)(2-methylprop-1-yl)phosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)(2,4-dipentoxyphenyl)phosphine oxide, bis(2,6-dimethoxybenzoyl)benzylphosphine oxide, bis(2,6-dimethoxybenzoyl) 2,6-dimethoxybenzoyl)-2-phenylpropylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylethylphosphine oxide, bis(2,6-dimethoxybenzoyl)benzylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylpropylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylethylphosphine oxide, 2,6-dimethoxybenzoylbenzylbutylphosphine oxide, 2,6-dimethoxybenzoylbenzyloctylphosphine oxide, bis(2,4,6-trimethylbenzoyl)isobutylphosphine oxide and 2,6-dimethoxybenzoyl-2,4,6-trimethylbenzoyl-n-butylphosphine oxide. Among these, bis(2,6-dimethoxybenzoyl)(2,4,4-trimethylpentyl)phosphine oxide or 2,4,6-trimethylbenzoyldiphenylphosphine oxide is preferred from the viewpoint of photocurability.
[0041] Examples of mono- and di-acylgermanium compounds include bisbenzoyldiethylgermanium, bisbenzoyldimethylgermanium, bisbenzoyldibutylgermanium, bis(4-methoxybenzoyl)dimethylgermanium, and bis(4-methoxybenzoyl)diethylgermanium, such as bis(4-methoxybenzoyl)diethylgermanium.
[0042] The curable composition of the present invention may further contain a polymerization accelerator to further improve the curability. Examples of the polymerization accelerator include aliphatic amines, aromatic amines, sulfinic acid derivatives, sulfur-containing reductive inorganic compounds, nitrogen-containing reductive inorganic compounds, borate compounds, barbituric acid derivatives, triazine compounds, and halogen compounds. The amount of the polymerization accelerator is preferably 0.01 to 5 parts by weight, more preferably 0.1 to 3 parts by weight, based on 100 parts by weight of the total amount of the polymerizable monomers.
[0043] Examples of the aliphatic amine include primary aliphatic amines such as n-butylamine, n-hexylamine, and n-octylamine; secondary aliphatic amines such as diisopropylamine and dibutylamine; and tertiary aliphatic amines such as N-methyldiethanolamine, N-ethyldiethanolamine, Nn-butyldiethanolamine, N-lauryldiethanolamine, 2-(dimethylamino)ethyl(meth)acrylate, N-methyldiethanolamine di(meth)acrylate, N-ethyldiethanolamine di(meth)acrylate, triethanolamine mono(meth)acrylate, triethanolamine di(meth)acrylate, triethanolamine tri(meth)acrylate, triethanolamine, trimethylamine, triethylamine, and tributylamine. Among these, tertiary aliphatic amines are preferred from the viewpoint of the curability and storage stability of the composition, and among these, 2-(dimethylamino)ethyl(meth)acrylate and N-methyldiethanolamine di(meth)acrylate are preferred.
[0044] Examples of the aromatic amine compound include 2,2-[3-(methylphenyl)imino]bisethanol acetate, 1,1-[(4-methylphenyl)imino]bis(2-propanol), p-tolyldiethanolamine, N,N-bis(2,2,2-trifluoroethyl)-p-toluidine, N,N-di(1-hydroxyethyl)-p-toluidine, N,N-di(2-hydroxypropyl)-p-toluidine, N-(1-cyanoethyl)-N-(1-acetoxyethyl)-m-toluidine, N,N-di(1-chloroethyl)-p-toluidine, N,N-dimethyl-p-toluidine, N-ethyl-N-methylaniline, N,N-dimethyl-aniline, N,N-dipropyl-o-toluidine, N,N-dipropyl-m-toluidine, N,N-dipropyl-p-toluidine, and ethyl 4-dimethylaminobenzoate. Among these aromatic amine compounds, it is preferable to use ethyl 4-dimethylaminobenzoate from the viewpoints of excellent solubility in polymerizable monomers and storage stability.
[0045] Examples of the sulfinic acid derivatives include salts of p-toluenesulfinic acid, benzenesulfinic acid, 2,4,6-trimethylbenzenesulfinic acid, 2,4,6-triethylbenzenesulfinic acid, 2,4,6-triisopropylbenzenesulfinic acid, and the like (preferably salts of alkali metals or alkaline earth metals). Specific examples of the salt compounds of these sulfinic acids include sodium p-toluenesulfinate and sodium benzenesulfinate.
[0046] Examples of reducing inorganic compounds containing sulfur include sulfites, bisulfites, pyrosulfites, thiosulfates, thionates, and dithionites. Specific examples include sodium sulfite, potassium sulfite, calcium sulfite, ammonium sulfite, sodium hydrogen sulfite, and potassium hydrogen sulfite.
[0047] The nitrogen-containing reducing inorganic compound may be a nitrite, and specific examples thereof include sodium nitrite, potassium nitrite, calcium nitrite, and ammonium nitrite.
[0048] The borate compounds include trialkylphenyl boron, trialkyl(p-chlorophenyl) boron, trialkyl(p-fluorophenyl) boron, trialkyl(3,5-bistrifluoromethyl) phenyl boron, trialkyl[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl) phenyl] boron, trialkyl(p-nitrophenyl) boron, trialkyl(m-nitrophenyl) boron, trialkyl(p-butylphenyl) boron, trialkyl(m-butylphenyl) boron, trialkyl(p-butyloxyphenyl) boron, trialkyl(m-butylphenyl) boron, Examples of the alkyl group include trialkyl(p-octyloxyphenyl)boron, trialkyl(p-octyloxyphenyl)boron and trialkyl(m-octyloxyphenyl)boron (wherein the alkyl group is at least one selected from the group consisting of an n-butyl group, an n-octyl group, an n-dodecyl group, and the like), as well as salts thereof (sodium salt, lithium salt, potassium salt, magnesium salt, tetrabutylammonium salt, tetramethylammonium salt, tetraethylammonium salt, methylpyridinium salt, ethylpyridinium salt, butylpyridinium salt, methylquinolinium salt, ethylquinolinium salt, butylquinolinium salt, and the like).
[0049] Barbituric acid derivatives include barbituric acid, 1,3-dimethylbarbituric acid, 1,3-diphenylbarbituric acid, 1,5-dimethylbarbituric acid, 5-butylbarbituric acid, 5-ethylbarbituric acid, 5-isopropylbarbituric acid, 5-cyclohexylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric acid, 1,3-dimethyl-5-isobutylbarbituric acid, 1,3-dimethylbarbituric acid, 1,3-dimethyl-5-cyclopentylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-1-ethylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 5-methylbarbituric acid, 5-propylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric acid, 1,3-dimethyl-5-isobutylbarbituric acid, 1,3-dimethylbarbituric acid, 1,3-dimethylbarbituric acid, 1,3-dimethyl-5-cyclopentylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-1-ethylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 5-methylbarbituric acid, 5-propylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric Examples of the salts of barbituric acids include 1,5-diethylbarbituric acid, 1-ethyl-5-methylbarbituric acid, 1-ethyl-5-isobutylbarbituric acid, 1,3-diethyl-5-butylbarbituric acid, 1-cyclohexyl-5-methylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-cyclohexyl-5-octylbarbituric acid, 1-cyclohexyl-5-hexylbarbituric acid, 5-butyl-1-cyclohexylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, and salts of thiobarbituric acids (preferably salts of alkali metals or alkaline earth metals). Specific examples of the salts of barbituric acids include sodium 5-butylbarbiturate, sodium 1,3,5-trimethylbarbiturate, and sodium 1-cyclohexyl-5-ethylbarbiturate.
[0050] The triazine compounds include 2,4,6-tris(trichloromethyl)-s-triazine, 2,4,6-tris(tribromomethyl)-s-triazine, 2-methyl-4,6-bis(trichloromethyl)-s-triazine, 2-methyl-4,6-bis(tribromomethyl)-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methylthiophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2 -(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2,4-dichlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-bromophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-n-propyl-4,6-bis(trichloromethyl)-s-triazine, 2-(α,α,β-trichloroethyl)-4,6-bis(trichloromethyl)-s-triazine, 2-styryl-4,6-bis( trichloromethyl)-s-triazine, 2-[2-(p-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(o-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(p-butoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(3,4-dimethoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(3,4,5-trimethoxyphenyl)ethenyl]-4,6 -Bis(trichloromethyl)-s-triazine, 2-(1-naphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-biphenylyl)-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N,N-bis(2-hydroxyethyl)amino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N-hydroxyethyl-N-ethylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N-hydroxyethyl-N-methylamino}ethoxy]-4,Examples of the 6-bis(trichloromethyl)-s-triazine include 2-[2-{N,N-diallylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine.
[0051] Examples of the halogen compound include dilauryl dimethyl ammonium chloride, lauryl dimethyl benzyl ammonium chloride, benzyl trimethyl ammonium chloride, tetramethyl ammonium chloride, benzyl dimethyl cetyl ammonium chloride, and dilauryl dimethyl ammonium bromide.
[0052] The curable composition of the present invention may contain a metal supplement to further improve storage stability. The curability of the curable composition of the present invention changes significantly due to contamination with a trace amount of metal element. In order to minimize the influence on the curability caused by the inclusion of a trace amount of metal element in the raw material or contamination with metal element during the manufacturing process, a metal supplement such as an aminocarboxylic acid chelating agent or a phosphonic acid chelating agent may be contained. Examples of the aminocarboxylic acid chelating agent include ethylenediaminetetraacetic acid or its sodium salt, nitrilotriacetic acid or its sodium salt, diethylenetriaminepentaacetic acid or its sodium salt, N-(2-hydroxyethyl)ethylenediaminetriacetic acid or its sodium salt, triethylenetetramineN,N,N',N'',N''',N'''-hexaacetic acid or its sodium salt, 1,3-propanediamine-N,N,N',N'-tetraacetic acid or its sodium salt, 1,3-diamino-2-propanol-N,N,N',N'-tetraacetic acid or its sodium salt, hydroxyethyliminodiacetic acid or its sodium salt, N,N-di(2-hydroxyethyl)glycine or its sodium salt, and glycol ether diaminetetraacetic acid or its sodium salt. Examples of the phosphonic acid chelating agent include etidronic acid or its sodium salt, nitrilotris(methylenephosphonic acid) or its sodium salt, and 2-phosphonobutane-1,2,4-tricarboxylic acid or its sodium salt. Among them, ethylenediaminetetraacetic acid or its sodium salt is preferred from the viewpoint of metal capture ability. A plurality of kinds of these metal supplements may be used in combination as necessary. From the viewpoint of curability, the amount of the metal supplement is preferably 1 part by weight or less based on the total amount of all polymerizable monomers, and if it exceeds 1 part by weight, the curability of the composition may decrease.
[0053] The polymerizable composition of the present invention may contain known additives, such as polymerization inhibitors, antioxidants, pigments, dyes, ultraviolet absorbers, organic solvents, thickeners, etc., within the limits of not impairing the properties of the composition.
[0054] The dental hardenable composition of the present invention can be a two-paste type consisting of a first paste and a second paste. In this case, the mixing ratio of the first paste to the second paste is usually 1:7 to 7:1, preferably 1:4 to 4:1, more preferably 1:2 to 2:1, and most preferably 1:1, in terms of volume ratio. The mixing ratio of the first paste to the second paste can be set within a range that satisfies the desired ratio of each component.
[0055] The dental curable composition of the present invention in the case of the two-paste type can be produced by a process of uniformly mixing the respective materials using a kneading device such as a double planetary mixer or a planetary mixer.
[0056] In the dental hardenable composition of the present invention, (a) the fourth period transition metal compound, (b) the thiourea derivative, and (c) the organic peroxide having a hydroperoxide group are essential for the initiation reaction of polymerization. The combination of the first and second pastes can be appropriately selected, but the first paste is preferably a mixture of (a) the fourth period transition metal compound, (b) the thiourea derivative, and (c) the organic peroxide having a hydroperoxide group. Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. It is preferable that the first paste contains a transition metal adsorbent having a fourth period transition metal compound adsorbed on inorganic particles, (b) a thiourea derivative, and (d) a polymerizable monomer, and the second paste contains (c) an organic peroxide having a hydroperoxide group, and (d) a polymerizable monomer. EXAMPLES
[0057] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. The abbreviations used below are as follows.
[0058] [Production of transition metal adsorbents] Fourth row transition metal compounds Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. The method for producing a transition metal adsorbent in which a fourth period transition metal compound is adsorbed on inorganic particles is as follows. (Transition metal adsorbent 1) The average particle size in the eggplant flask was 4.5 μm, the pore volume was 0.06 cc / g, and the specific surface area was 5.2 m 2 10 g of barium sulfate (BMH-40: manufactured by Sakai Chemical Industry Co., Ltd.) with a molecular weight of 0.0192 g / m2 and 1 g of vanadyl acetylacetonate (hereinafter, VOA: Tokyo Chemical Industry Co., Ltd.) were added to 20 g of absolute ethanol and dispersed in an ultrasonic cleaner for 10 minutes. After that, the ethanol was removed under reduced pressure using an evaporator, and the mixture was dried in vacuum for 24 hours to obtain a 0.0192 g / m2 solution. 2 Thus, a transition metal adsorbent 1 was obtained, in which the transition metal compound was adsorbed on the surface. (Transition metal adsorbent 2) The pot contains an average particle size of 0.2 μm, a pore volume of 0.05 cc / g, and a specific surface area of 8.1 m 2 After adding 10 g of trifluoride (Treibach) with a molecular weight of 0.0124 g / m and 1 g of VOA, 200 g of φ2 mm alumina balls were added and processed at 200 rpm for 2 minutes in a planetary mill (Fritsch: P-5 planetary ball mill classic line), and then passed through a #200 mesh to obtain a 0.0124 g / m 2 Thus, a transition metal adsorbent 2 was obtained, in which the transition metal compound was adsorbed on the surface. (Transition metal adsorbent 3) The flask contained an average particle size of 12.0 μm, a pore volume of 0.04 cc / g, and a specific surface area of 2.2 m 2 10 g of barium sulfate (BMH-10: manufactured by Sakai Chemical Industry Co., Ltd.) with a molecular weight of 0.0454 g / m2 and 1 g of vanadium oxide stearate (hereinafter referred to as VOS: manufactured by Tokyo Chemical Industry Co., Ltd.) were added to 20 g of absolute ethanol and dispersed in an ultrasonic cleaner for 10 minutes. After that, the ethanol was removed under reduced pressure using an evaporator, and the mixture was dried in vacuum for 24 hours to obtain a 0.0454 g / m2 solution. 2 Thus, a transition metal adsorbent 3 having the transition metal compound adsorbed on its surface was obtained. (Transition metal adsorbent 4) The average particle size in the eggplant flask was 0.015 μm, the pore volume was 0.09 cc / g, and the specific surface area was 90 m 2 10 g of barium sulfate (BF-40: manufactured by Sakai Chemical Industry Co., Ltd.) with a molecular weight of 0.00111 g / m and 1 g of VOA were added to 20 g of absolute ethanol and dispersed in an ultrasonic cleaner for 10 minutes. After that, the ethanol was removed under reduced pressure using an evaporator, and the mixture was dried in vacuum for 24 hours to obtain a 0.00111 g / m 2Thus, a transition metal adsorbent 4 was obtained, having the transition metal compound adsorbed on its surface. (Transition metal adsorbent 5) The average particle size in the eggplant flask was 4.5 μm, the pore volume was 0.06 cc / g, and the specific surface area was 5.2 m 2 10 g of barium sulfate (BMH-40: manufactured by Sakai Chemical Industry Co., Ltd.) with a molecular weight of 0.03846 g / m2 and 2 g of VOA were added to 20 g of absolute ethanol and dispersed in an ultrasonic cleaner for 10 minutes. After that, the ethanol was removed under reduced pressure using an evaporator, and the mixture was dried in vacuum for 24 hours to obtain a molecular weight of 0.03846 g / m2. 2 Thus, a transition metal adsorbent 5 having the transition metal compound adsorbed on its surface was obtained. (Transition metal adsorbent 6) The average particle size in the eggplant flask was 4.5 μm, the pore volume was 0.06 cc / g, and the specific surface area was 5.2 m 2 50 g of barium sulfate (BMH-40: manufactured by Sakai Chemical Industry Co., Ltd.) with a molecular weight of 0.00385 g / m and 1 g of VOA were added to 20 g of absolute ethanol and dispersed in an ultrasonic cleaner for 10 minutes. After that, the ethanol was removed under reduced pressure using an evaporator, and the mixture was dried in vacuum for 24 hours to obtain a 0.00385 g / m 2 Thus, a transition metal adsorbent 6 was obtained, in which the transition metal compound was adsorbed on the surface. (Transition metal adsorbent 7) The pot contains an average particle size of 1.4 μm, a pore volume of 0.01 cc / g, and a specific surface area of 4.2 m 2 After adding 10 g of spherical silica particles (SO-C6: manufactured by ADMAFINE) with a molecular weight of 0.0238 g / m and 1 g of VOA, 200 g of alumina balls with a diameter of 2 mm were added and processed at 200 rpm for 2 minutes in a planetary mill (Fritsch: P-5 planetary ball mill classic line), and then passed through a #200 mesh to obtain a 0.0238 g / m 2 Thus, transition metal adsorbent 7 was obtained, having the transition metal compound adsorbed on its surface. (Transition metal adsorbent 8) The pot contains an average particle size of 0.3 μm, a pore volume of 0.01 cc / g, and a specific surface area of 14.6 m 2After adding 10 g of spherical silica particles (SO-C1: manufactured by ADMAFINE) with a molecular weight of 0.0137 g / m and 2 g of VOA, 200 g of φ2 mm alumina balls were added and processed at 200 rpm for 2 minutes in a planetary mill (Fritsch: P-5 planetary ball mill classic line), and then passed through a #200 mesh to obtain a 0.0137 g / m 2 Thus, a transition metal adsorbent 8 was obtained, having the transition metal compound adsorbed on its surface. (Transition metal adsorbent 9) The pot contains an average particle size of 0.5 μm, a pore volume of 0.11 cc / g, and a specific surface area of 12.3 m 2 Add 10 g of aluminosilicate glass particles (SiO2 32.2%, Al2O3 19.3%, SrO2 6.9%, F8.7%, Na2O4.0%, B2O3 8.9%, Matsukaze, crushed product) with a molecular weight of 0.0081 g / m2 and 1 g of VOA, then add 200 g of φ2 mm alumina balls, process in a planetary mill (Fritsch: P-5 planetary ball mill classic line) at 200 rpm for 2 minutes, and pass through a #200 mesh to obtain a 0.0081 g / m2 powder. 2 Thus, a transition metal adsorbent 9 was obtained, having the transition metal compound adsorbed on its surface. (Transition metal adsorbent 10) The pot contains an average particle size of 3 μm, a pore volume of 0.21 cc / g, and a specific surface area of 120 m 2 Add 10 g of porous silica zirconia particles (SiO2 92.1%, ZrO 7.8%, others 0.1%, Matsukaze Manufacturing) with a molecular weight of 0.00417 g / m2 and 5 g of VOA, then add 200 g of φ2 mm alumina balls, process at 200 rpm for 2 minutes in a planetary mill (Fritsch: P-5 planetary ball mill classic line), and pass through a #200 mesh to obtain a 0.00417 g / m2 mixture. 2 Thus, a transition metal adsorbent 10 was obtained, having the transition metal compound adsorbed on its surface. (Transition metal adsorbent 11) The flask contained an average particle size of 12.0 μm, a pore volume of 0.04 cc / g, and a specific surface area of 2.2 m 2 10 g of barium sulfate (BMH-10: manufactured by Sakai Chemical Industry Co., Ltd.) with a molecular weight of 0.09091 g / m and 2 g of VOS were added to 20 g of absolute ethanol and dispersed in an ultrasonic cleaner for 10 minutes. After that, the ethanol was removed under reduced pressure using an evaporator, and the mixture was dried in vacuum for 24 hours to obtain a 0.09091 g / m 2Thus, a transition metal adsorbent 11 was obtained, having the transition metal compound adsorbed on its surface. (Transition metal adsorbent 12) The average particle size in the eggplant flask was 0.015 μm, the pore volume was 0.09 cc / g, and the specific surface area was 90 m 2 20 g of barium sulfate (BF-40: manufactured by Sakai Chemical Industry Co., Ltd.) with a molecular weight of 0.00056 g / m and 1 g of VOA were added to 20 g of absolute ethanol and dispersed in an ultrasonic cleaner for 10 minutes. After that, the ethanol was removed under reduced pressure using an evaporator, and the mixture was dried in vacuum for 24 hours to obtain a 0.00056 g / m 2 Thus, a transition metal adsorbent 12 was obtained, having the transition metal compound adsorbed on its surface. (Transition metal adsorbent 13) The average particle size in the eggplant flask is 8.3 μm, and the specific surface area is 4.3 m 2 10 g of PMMA particles (MB-8C: Sekisui Chemical Co., Ltd.) with a molecular weight of 0.0233 g / m and 1 g of VOS were added to 50 g of absolute ethanol and dispersed in an ultrasonic cleaner for 10 minutes. After that, the ethanol was removed under reduced pressure using an evaporator, and the mixture was dried in vacuum for 24 hours to obtain a 0.0233 g / m 2 Thus, a transition metal adsorbent 13 having the transition metal compound adsorbed on its surface was obtained. (Transition metal adsorbent A) The average particle size in the pot is 8.1 μm, and the specific surface area is 86 m 2 After adding 10 g of porous cross-linked PMMA particles (MBP-8: Sekisui Chemical Co., Ltd.) with a molecular weight of 1 / g and 2 g of VOA, 200 g of alumina balls with a diameter of 2 mm were added and processed at 200 rpm for 2 minutes in a planetary mill (Fritsch: P-5 Planetary Ball Mill Classic Line). Although the material was removed from the pot, it was confirmed that it could not be used as an adsorbent because it had strongly aggregated and formed a lump.
[0059] [(b) Thiourea derivatives] ATU: N-acetylthiourea BTU: N-benzoylthiourea
[0060] [(c) Organic peroxide having a hydroperoxide group] CHP: Cumene hydroperoxide t-BHP: t-butyl hydroperoxide
[0061] [(d-1) Polymerizable monomer having no acidic group] Bis-GMA: 2,2-bis[4-(3-methacryloyloxy)-2-hydroxypropoxyphenyl]propane UDMA: 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate 2.6E: 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane with an average molar number of ethoxy groups of 2.6 TEGDMA: Triethylene glycol dimethacrylate NPG: Neopentyl glycol dimethacrylate 2-HEMA: 2-hydroxyethyl methacrylate GDMA: glycerol dimethacrylate
[0062] [(d-2) Polymerizable monomer having an acidic group] MDP: 10-methacryloyloxydecyl dihydrogen phosphate 6-MHPA: (6-methacryloyloxy)hexyl phosphonoacetate 4-MET: 4-methacryloyloxyethyl trimellitate
[0063] [Filler 1] To 100.0 g of glass filler (GM344923: average particle size: 0.8 μm) manufactured by Schott, 10.0 g of water, 80.0 g of ethanol, 0.020 g of phosphoric acid, and 10.0 g of 3-methacryloyloxypropyltrimethoxysilane as a silane coupling agent were stirred at room temperature for 2 hours, and the silane coupling treatment liquid obtained was added and stirred for 30 minutes. After that, heat treatment was performed at 140°C for 15 hours to obtain filler 1. [Filler 2] To 100.0 g of spherical silica filler (SO-C2: average particle size: 0.5 μm) manufactured by Admatechs Co., Ltd., 10.0 g of water, 80.0 g of ethanol, 0.020 g of phosphoric acid, and 5.0 g of 3-methacryloyloxypropyltrimethoxysilane as a silane coupling agent were stirred at room temperature for 2 hours, and the silane coupling treatment liquid obtained was added and stirred and mixed for 30 minutes. After that, heat treatment was performed at 140°C for 15 hours to obtain filler 2.
[0064] [others] CQ: Camphorquinone (photopolymerization initiator) APO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide (photopolymerization initiator) BHT: 2,6-di-t-butyl-4-methylphenol (polymerization inhibitor) EDTA: Sodium ethylenediaminetetraacetate (metal supplement) DMBE: Ethyl 4-dimethylaminobenzoate (polymerization accelerator) VOA: Vanadyl acetylacetonate (same material as used for transition metal adsorbents)
[0065] [Paste manufacturing method] For each of the first paste or second paste shown in Tables 1 to 3, (b) thiourea derivative, (c) organic peroxide having a hydroperoxide group, (d) polymerizable monomer without an acidic group, (e) polymerizable monomer having an acidic group, and others were added to a mixing vessel, and mixed at 100 rpm for 24 hours using a mix rotor VMRC-5 to obtain a resin liquid. Then, the filler, (a) the 4th period transition metal compound, and the like were added to the mixing vessel. Other than adsorption Non-reactive and selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, and composite oxides thereof, metal fluorides, and sulfates. The transition metal adsorbent, in which a transition metal compound of the fourth period is adsorbed on inorganic particles, was placed in a kneading container and kneaded for 20 minutes at 1400 rpm using a planetary centrifugal mixer ARV-300 to obtain a first paste and a second paste. The first paste and the second paste obtained were filled in a 5 mL double syringe (volume ratio of the first paste to the second paste is 1:1) manufactured by Mixpack Co., Ltd., so as to have a predetermined weight component ratio, and compositions 1 to 31 were prepared as dental two-paste type polymerizable compositions.
[0066] [Method of measuring average particle size] Using a particle size analyzer Microtrac MT3300EXII (manufactured by Nikkiso), the inorganic particles were subjected to ultrasonic waves for 1 minute, and then the particle size was measured. For samples with an average particle size of 200 nm or less, a photograph of the inorganic particles was taken at an arbitrary magnification using a scanning electron microscope (Hitachi Science Systems Co., Ltd.: SEMEDX3 TypeN), the photographed image was processed using image analysis software, the circle equivalent diameter of 50 primary particles was measured, and the average particle size was calculated using the above formula based on the measured value.
[0067] [Method of measuring pore volume and specific surface area] Using a QUADRASORB evo (manufactured by QUAUTACHORME), the specific surface area was measured by the BET multipoint method, and the pore volume was measured by the BJH method. Note that the inorganic particles were pretreated (heated at 200°C and vacuum degassed for 2 hours) to remove adsorbed moisture before measurement.
[0068] [Table 1] [Table 2] [Table 3]
[0069] The test methods for the properties evaluated in the examples and comparative examples are as follows. Each test was performed under automatic mixing conditions with a mixing tip attached.
[0070] [Curing time measurement] The setting time of the kneaded product of Paste A and B is measured in accordance with ISO4049:2009. Specifically, 0.8 g of the kneaded paste is filled into a container (4 mmφ x 6 mm: Teflon) equipped with a thermocouple, and the heat generation curve due to the setting reaction is recorded. The setting time is the time from the start of kneading the paste to the peak of the heat generation curve, and the measured values for three runs are averaged.
[0071] [Curing stability] The above-mentioned hardening times were compared immediately after preparation of the paste and after storage at 40°C for 5 months, and a change rate of less than ±20% was rated as S, 20% to less than 40% or -20% to less than -40% as A, 40% to less than 60% or -40% to less than -60% as B, and gelation or unhardened, etc. as C. Change rate (%) = [(Curing time after storage at 40°C for 5 months / Curing time immediately after preparation) - 1] x 100
[0072] [Paste stability] <Color difference> The paste was discharged from the syringe, and the color tone (CIE L*a*b*) of the paste containing the transition metal compound was measured immediately after preparation and after storage at 40°C for 5 months, and the color difference ΔE was calculated. ΔE of 0 or more and less than 2 was rated as S, 2 or more and less than 4 was rated as A, 4 or more and less than 8 was rated as B, and 8 or more was rated as C. Regarding the specific color measurement method, the paste was taken into a mold with a thickness of 1.0 mm and an inner diameter of 15 mm, and both ends were fixed with a thin glass plate with a thickness of 0.15±0.02 mm, and the color was measured at a thickness of 1.0 mm using a spectrophotometer (CM-26d: manufactured by Konica Minolta) under the conditions of SCE and white background. <Properties> Equal amounts of the first and second pastes were discharged from the syringes, and the feel of the paste was checked using a spatula. Pastes that showed no change between immediately after preparation and after storage at 40°C for 5 months were rated as A, those that had hardened slightly were rated as B, and those that showed obvious changes such as gelation that made them difficult to use were rated as C.
[0073] The above-mentioned test results were carried out for compositions 1 to 48, and the results are shown in Table 4. Compositions 1 to 17, 21, 22, 25 to 30, and 32 to 46, which satisfy the storage stability and color stability, are described as Examples 1 to 40, respectively.
[0074] [Table 4]
[0075] Examples 1 to 40, in which each component satisfies the constitution shown in the present invention, harden even after storage at 40°C for 5 months, do not show a significant change in color tone, and have high storage stability because they are sufficiently durable for use as dental compositions applied to the oral cavity. In addition, in Examples 7, 11, 14 to 16, 18 to 25, 37, and 38, although shortening or delay in hardening time was observed after storage at 40°C for 5 months, it was confirmed that this was not a significant change in operation.
[0076] Although the reason for this is unclear for Example 11, it is presumed that the polymerization promoting effect is reduced due to the absence of (d-2) a polymerizable monomer having an acidic group.
[0077] In Examples 7, 14, 15, and 16, it is presumed that the reactivity of the transition metal compounds adsorbed on the spherical silica or fluoroaluminosilicate glass was reduced for some reason.
[0078] In Examples 18 and 19, the curing time was shortened after storage for 5 months at 40° C. This is believed to be due to the excessive blending amount of (b) thiourea derivative or (c) organic peroxide having a hydroperoxide group.
[0079] In Examples 20 and 38, it is believed that the shortening or delay in curing time occurred due to the fact that the transition metal compound was contained in a slightly excessive amount relative to (b) the thiourea derivative and (c) the organic peroxide having a hydroperoxide group.
[0080] In Examples 22, 24, and 26, the amount of adsorbed transition metal was somewhat large, and it is presumed that the transition metal compound was localized in the composition, causing slight discoloration.
[0081] In Examples 21, 23, and 37, a slight delay in the curing time was observed after storage for 5 months at 40° C. It is presumed that in Example 21, the transition metal compound itself was insufficient relative to (b) the thiourea derivative and (c) the organic peroxide having a hydroperoxide group, and that in Example 23, the amount of adsorbed transition metal in the transition metal adsorbent was insufficient.
[0082] Example 25 is a composition in which (b) the thiourea derivative and (c) the organic peroxide having a hydroperoxide group of Example 16 are replaced with each other from their respective pastes, and an acceptable shortening of the curing time is observed. This is presumably due to the unintended increase in activity of (c) the organic peroxide having a hydroperoxide group and the transition metal compound being mixed in the same paste for a long period of time.
[0083] In Example 28, it is presumed that the amount of (b) thiourea derivative was slightly small, which caused some discoloration.
[0084] In Example 30, it is presumed that the amount of (b) thiourea derivative was somewhat large, which caused some discoloration.
[0085] In Example 32, it is presumed that the amount of (c) organic peroxide having a hydroperoxide group was slightly small, which caused some discoloration.
[0086] In Example 36, it is presumed that the amount of (d-2) the polymerizable monomer having an acidic group was somewhat large, which caused slight discoloration.
[0087] As for Example 40, since it did not contain any components other than (a) to (d), it is presumed that slight discoloration occurred and the paste properties deteriorated.
[0088] The hardening time of these dental compositions can be adjusted as desired by adding multiple polymerization accelerators or by increasing or decreasing the blending amount or the adsorption amount of the transition metal compound. Furthermore, since it is possible to adjust physical properties such as bending strength, bending modulus, and coating thickness by appropriately changing the blending amount and particle size of the filler, these compositions are suitable for use as dental two-paste polymerizable compositions such as dental cements, dental adhesives, dental self-polymerizing resins, dental core building materials, and dental use.
[0089] In Comparative Example 1, since no transition metal compound was blended, the polymerization promoting effect was not obtained, and the curing time immediately after preparation was extremely long. Furthermore, it was confirmed that the composition did not cure even after storage at 40°C for 5 months.
[0090] In Comparative Examples 2 and 3, no significant change was observed in the curing time, but discoloration of the composition was observed after storage for 5 months at 40° C. It is presumed that the discoloration was caused by the transition metal compounds adsorbed in the pores remaining for a long period of time.
[0091] In Comparative Example 4, discoloration was observed after storage at 40°C for 5 months, and in Comparative Example 5, gelation was observed after storage at 40°C for 5 months. It is presumed that this is because the transition metal compound was dispersed in the paste without being adsorbed to inorganic particles, etc., and was localized microscopically, which led to discoloration or gelation. In addition, although the blending amount of the transition metal compound in Comparative Example 4 was almost the same as that in Example 1, the long curing time suggests that the dispersion in the composition was insufficient.
[0092] In Comparative Example 6, the hardening time immediately after preparation was appropriate, but it was confirmed that the first paste gelled after storage at 40°C for 5 months. Although the blending amount of the transition metal compound was the same as in Example 1, it is considered that the PMMA particles, which are the adsorption particles, were swelled or dissolved in the polymerizable monomer, and the dispersed state was broken, and the transition metal compound was localized in the composition, inducing gelation. In Comparative Examples 7 and 8, hardening did not occur. [Industrial Applicability]
[0093] INDUSTRIAL APPLICABILITY The present invention is widely used in the dental field as dental resin cements, dental abutment construction materials, dental adhesives, dental coating materials, pit and fissure sealing materials, composite resins, dental self-polymerizing resins, dental pretreatment materials, denture base materials, etc., and therefore can be industrially applied.
Claims
1. (a) a transition metal adsorbent which is non-reactive with a fourth period transition metal compound in any manner other than by adsorption, and which has a fourth period transition metal compound adsorbed on inorganic particles selected from the group consisting of silica, zirconia, calcium oxide, titania, alumina, composite oxides thereof, metal fluorides, and sulfates; (b) one or more thiourea derivatives selected from the group consisting of dimethylthiourea, diethylthiourea, tetramethylthiourea, (2-pyridyl)thiourea, N-methylthiourea, ethylenethiourea, N-allylthiourea, N-allyl-N'-(2-hydroxyethyl)thiourea, N-benzylthiourea, 1,3-dicyclohexylthiourea, N,N'-diphenylthiourea, 1,3-di(p-tolyl)thiourea, 1-methyl-3-phenylthiourea, N-acetylthiourea, N-benzoylthiourea, diphenylthiourea, and dicyclohexylthiourea; (c) an organic peroxide having a hydroperoxide group, and (d) a polymerizable monomer, The (d) polymerizable monomer includes (d-1) a polymerizable monomer having no acidic group, The pore volume of the inorganic particles is 0.2 cc / g or less, A dental hardenable composition, characterized in that the fourth period transition metal compound is a vanadium compound.
2. A dental hardenable composition as described in claim 1, wherein the (d) polymerizable monomer further contains (d-2) a polymerizable monomer having an acidic group.
3. A dental hardenable composition as described in claim 2, containing 1 to 40 parts by weight of (d-2) a polymerizable monomer having an acidic group per 100 parts by weight of the total amount of (d) the polymerizable monomer.
4. The first paste The (a) transition metal adsorbent, (b) a thiourea derivative, and (d) the polymerizable monomer; The second paste (c) an organic peroxide having a hydroperoxide group, and 4. The dental hardenable composition according to claim 1, further comprising the polymerizable monomer (d).
5. The adsorption amount of the 4th period transition metal compound in the (a) transition metal adsorbent is 0.001 to 0.1 g / m 2 5. The dental hardenable composition according to claim 1, wherein
6. For 100 parts by weight of the total amount of polymerizable monomers, 0.05 to 7.5 parts by weight of the (a) transition metal adsorbent, (a) 0.001 to 1 part by weight of a transition metal compound contained in the transition metal adsorbent; 0.1 to 4 parts by weight of the (b) thiourea derivative, (c) 0.1 to 3 parts by weight of an organic peroxide having a hydroperoxide group The dental hardenable composition according to any one of claims 1 to 5, comprising:
7. For 100 parts by weight of the total amount of polymerizable monomers, 0.5 to 350 parts by weight of filler, 0.01 to 5 parts by weight of photopolymerization initiator, 7. The dental hardenable composition according to claim 6, further comprising 0.01 to 5 parts by weight of a polymerization accelerator.
Citation Information
Patent Citations
Adhesive kit
JP2004043427A
Curable composition for dental use
JP2009292761A
Polymerizable composition
JP2012051856A
Adherent composition for polyaryletherketone resin material
JP2017110162A
Dental composition and kit for dental prosthesis adhesion
JP2019112343A